REPRESENTATION OF GENDER INJUSTICE IN THE NOVEL BROKEN STRINGS BY AURELIE MOEREMANS A STUDY OF LITERARY FEMINISM - Julhijah Julhijah; Nina Queena Hadi Putri; Alfian Rokmansyah; Nia Novita Putri (Universitas Muhammadiyah Makassar, 2026)
Gender inequality is formed through a process of social construction that develops within a patriarchal system and is manifested in various manifestations of unequal relations between men and women. The literary work Broken Strings illustrates this reality through the narratives of its female characters. This study aims to analyze the various manifestations of gender inequality experienced by the female characters in the novel, adopting the theoretical framework of feminism developed by Mansour Fakih. This study uses a descriptive, analytical, qualitative approach as its primary methodology. Primary data were obtained from the entire text of the novel Broken Strings, and data collection was conducted using library research methods. Data analysis was carried out through the stages of identification, categorization, and interpretation of quotations, indicating the presence of gender inequality, in line with Mansour Fakih's conceptual framework, which includes five aspects: marginalization, subordination, stereotypes, violence, and double workload. The research findings reveal that the female characters in the novel experience marginalization in access to social and economic resources, subordination in family decision-making, and stereotypes that hinder their freedom and identity formation. This study also identifies forms of symbolic and psychological violence that function as instruments of patriarchal control. The phenomenon of the double burden of work is clearly visible in the pressure of domestic responsibilities that remain attached to women, along with social obligations, without a fair and equal division of roles. The results of this study confirm that the novel Broken Strings presents a critique of patriarchal structures through depictions of unequal power relations and the transformation of consciousness and resistance the female characters undergo against the various forms of oppression they experience.